Corrigendum to “Vascular endothelium as a target for perfluroalkyl substances (PFAs)” [Environ. Res. 212 (2022) 1–4/11339] - Sharine Wittkopp; Fen Wu; Joseph Windheim; Morgan Robinson; Kurunthachalam Kannan; Stuart D. Katz; Yu Chen; Jonathan D. Newman (Environmental Research, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Using structured eradication feasibility assessment to prioritize the management of new and emerging invasive alien species in Europe - Olaf Booy; Pete A. Robertson; Niall Moore; Jess Ward; Helen E. Roy; Tim Adriaens; Richard Shaw; Johan Van Valkenburg; Gabrielle Wyn; Sandro Bertolino; Olivier Blight; Etienne Branquart; et al. (Global Change Biology, 2020)
Prioritizing the management of invasive alien species (IAS) is of global importance and within Europe integral to the EU IAS regulation. To prioritize management effectively, the risks posed by IAS need to be assessed, but so too does the feasibility of their management. While the risk of IAS to the EU has been assessed, the feasibility of management has not. We assessed the feasibility of eradicating 60 new (not yet established) and 35 emerging (established with limited distribution) species that pose a threat to the EU, as identified by horizon scanning. The assessment was carried out by 34 experts in invasion management from across Europe, applying the Non‐Native Risk Management scheme to defined invasion scenarios and eradication strategies for each species, assessing the feasibility of eradication using seven key risk management criteria. Management priorities were identified by combining scores for risk (derived from horizon scanning) and feasibility of eradication. The results show eradication feasibility score and risk score were not correlated, indicating that risk management criteria evaluate different information than risk assessment. In all, 17 new species were identified as particularly high priorities for eradication should they establish in the future, whereas 14 emerging species were identified as priorities for eradication now. A number of species considered highest priority for eradication were terrestrial vertebrates, a group that has been the focus of a number of eradication attempts in Europe. However, eradication priorities also included a diverse range of other taxa (plants, invertebrates and fish) suggesting there is scope to broaden the taxonomic range of attempted eradication in Europe. We demonstrate that broad scale structured assessments of management feasibility can help prioritize IAS for management. Such frameworks are needed to support evidence‐based decision‐making.

Polarity, planes of cell division, and the evolution of plant multicellularity - Karl J. Niklas; Randy Wayne; Mariana Benítez; Stuart A. Newman (Protoplasma, 2019)

A boreal songbird's 20,000 km migration across North America and the Atlantic Ocean - William V. DeLuca; Bradley K. Woodworth; Stuart A. Mackenzie; Amy E. M. Newman; Hilary A. Cooke; Laura M. Phillips; Nikole E. Freeman; Alex O. Sutton; Lila Tauzer; Carol McIntyre; Iain J. Stenhouse; Scott Weidensaul; et al. (Ecology, 2019)

Sleeper cells: the stringent response and persistence in the Borreliella ( Borrelia ) burgdorferi enzootic cycle - Felipe C. Cabello; Henry P. Godfrey; Julia V. Bugrysheva; Stuart A. Newman (Environmental Microbiology, 2017)
Summary Infections with tick‐transmitted Borreliella ( Borrelia ) burgdorferi , the cause of Lyme disease, represent an increasingly large public health problem in North America and Europe. The ability of these spirochetes to maintain themselves for extended periods of time in their tick vectors and vertebrate reservoirs is crucial for continuance of the enzootic cycle as well as for the increasing exposure of humans to them. The stringent response mediated by the alarmone (p)ppGpp has been determined to be a master regulator in B . burgdorferi . It modulates the expression of identified and unidentified open reading frames needed to deal with and overcome the many nutritional stresses and other challenges faced by the spirochete in ticks and animal reservoirs. The metabolic and morphologic changes resulting from activation of the stringent response in B . burgdorferi may also be involved in the recently described non‐genetic phenotypic phenomenon of tolerance to otherwise lethal doses of antimicrobials and to other antimicrobial activities. It may thus constitute a linchpin in multiple aspects of infections with Lyme disease borrelia, providing a link between the micro‐ecological challenges of its enzootic life‐cycle and long‐term residence in the tissues of its animal reservoirs, with the evolutionary side effect of potential persistence in incidental human hosts.

Blastocyst genotyping for quality control of mouse mutant archives: an ethical and economical approach - Ferdinando Scavizzi; Edward Ryder; Stuart Newman; Marcello Raspa; Diane Gleeson; Hannah Wardle-Jones; Lluis Montoliu; Almudena Fernandez; Marie-Laure Dessain; Vanessa Larrigaldie; Zuzana Khorshidi; Reetta Vuolteenaho; et al. (Transgenic Research, 2015)

Introduction: E Pluribus Unum - Vidyanand Nanjundiah; Stuart A Newman (Journal of Biosciences, 2014)

Limb, tooth, beak: Three modes of development and evolutionary innovation of form - Marta Linde-Medina; Stuart A Newman (Journal of Biosciences, 2014)

Rapid conversion of EUCOMM/KOMP-CSD alleles in mouse embryos using a cell-permeable Cre recombinase - Edward Ryder; Brendan Doe; Diane Gleeson; Richard Houghton; Priya Dalvi; Evelyn Grau; Bishoy Habib; Evelina Miklejewska; Stuart Newman; Debarati Sethi; Caroline Sinclair; Sapna Vyas; et al. (Transgenic Research, 2014)

Cell state switching factors and dynamical patterning modules: complementary mediators of plasticity in development and evolution - Stuart A. Newman; Ramray Bhat; Nadejda V. Mezentseva (Journal of Biosciences, 2009)

Phenotypic and Developmental Plasticity - Vidyanand Nanjundiah; Stuart A. Newman (Journal of Biosciences, 2009)

Snakes and ladders: the ups and downs of animal segmentation - Ramray Bhat; Stuart A. Newman (Journal of Biosciences, 2009)

Cell state switching factors and dynamical patterning modules: complementary mediators of plasticity in development and evolution - Stuart A. Newman; Ramray Bhat; Nadejda V. Mezentseva (Journal of Biosciences, 2009)

Genes and proteins: Dogmas in decline - Stuart A. Newman; Ramray Bhat (Journal of Biosciences, 2007)

The pre-Mendelian, pre-Darwinian world: Shifting relations between genetic and epigenetic mechanisms in early multicellular evolution - Stuart A. Newman (Journal of Biosciences, 2005)

Foreword - Vidyanand Nanjundiah; Stuart A. Newman; Scott F. Gilbert (Journal of Biosciences, 2005)

Stephen Jay Gould - Stuart A. Newman (Journal of Biosciences, 2002)

Developmental mechanisms: putting genes in their place - Stuart A Newman (Journal of Biosciences, 2002)

Susceptibility of Antarctic krill ( Euphausia superba Dana) to ultraviolet radiation - Stuart J. Newman; Stephen Nicol; David Ritz; Harvey Marchant (Polar Biology, 1999)